2020
DOI: 10.3390/en13030612
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Efficiency of PEM Electrolyzers through Membrane-Specific Pressure Optimization

Abstract: Hydrogen produced in a polymer electrolyte membrane (PEM) electrolyzer must be stored under high pressure. It is discussed whether the gas should be compressed in subsequent gas compressors or by the electrolyzer. While gas compressor stages can be reduced in the case of electrochemical compression, safety problems arise for thin membranes due to the undesired permeation of hydrogen across the membrane to the oxygen side, forming an explosive gas. In this study, a PEM system is modeled to evaluate the membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…High Faraday's efficiency can be explained by the fact that recently, PEM electrolyzers have been designed with technical improvements compared to the Faraday's efficiency obtained for alkaline electrolyzers in the 1990s. By increasing the hydrogen output pressure, the Faraday's efficiency is lower due to higher crossover currents through the membrane, corroborating the results obtained in previous works [29][30][31]. The effects of higher pressures are particularly noticeable at low current densities; whereas from 25 A (i.e., 0.5 A.cm 2 ), Faraday's efficiency is similar for the three tests.…”
Section: Analysis Of the Faraday's Efficiency Based On The Cathode Gasupporting
confidence: 89%
See 4 more Smart Citations
“…High Faraday's efficiency can be explained by the fact that recently, PEM electrolyzers have been designed with technical improvements compared to the Faraday's efficiency obtained for alkaline electrolyzers in the 1990s. By increasing the hydrogen output pressure, the Faraday's efficiency is lower due to higher crossover currents through the membrane, corroborating the results obtained in previous works [29][30][31]. The effects of higher pressures are particularly noticeable at low current densities; whereas from 25 A (i.e., 0.5 A.cm 2 ), Faraday's efficiency is similar for the three tests.…”
Section: Analysis Of the Faraday's Efficiency Based On The Cathode Gasupporting
confidence: 89%
“…The generated hydrogen is stored in three metal hydride tanks (not shown in Figure 4). The investigated PEM Finally, in [17,[29][30][31], compared to results reported in [10,15,16] for alkaline electrolyzers, the authors have shown that the temperature slightly affects the Faraday's efficiency of PEM electrolyzers. However, membrane thickness and gas pressure have a strong influence on the Faraday's efficiency.…”
Section: Description Of the Experimental Test Benchmentioning
confidence: 91%
See 3 more Smart Citations